2019
DOI: 10.26565/2220-637x-2019-33-01
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of enhanced oxidation ability of dilute nitric acid and dissolution of pure gold in seawater with nitric acid

Abstract: It has been discovered that dilute nitric acid in reversed micelle systems can oxidize the Br ion to Br 2 and we have proposed that the nitryl (or nitronium) ion NO 2 + should be the active species in the oxidation process. Nitration of phenol in reversed micelle systems with dilute nitric acid, CHCl 3 /CTAC/H 2 O (2.0 mol dm-3 HNO 3 in the 1.0% (v/v) H 2 O phase), has been performed at 35 ºC to obtain 2-and 4-nitrophenols, where CTAC represents cetyltrimethylammonium chloride. In aqueous 2.0 mol dm-3 HNO 3 so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The continuous formation of the gold complex drives the reaction and generates H 2 O and NO as byproducts, the latter combining with ambient oxygen to generate NO 2 . Some studies have suggested that HNO 3 may not be the only oxidizing agent in the reaction, as chlorine gas and nitrosyl chloride (produced during the reaction with aqua regia) can also oxidize small amounts of gold [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The continuous formation of the gold complex drives the reaction and generates H 2 O and NO as byproducts, the latter combining with ambient oxygen to generate NO 2 . Some studies have suggested that HNO 3 may not be the only oxidizing agent in the reaction, as chlorine gas and nitrosyl chloride (produced during the reaction with aqua regia) can also oxidize small amounts of gold [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%